PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS XI SMK NEGERI 9 PADANG - Marizal, Yulia; Hafrison, Mhd. (Universitas Negeri Padang, 2020)
ABSTRACT The purpose of this study is as follows. First, it describes the level of explanatory text writing skills of grade XI students of SMK Negeri 9 Padang before using the problem based learning model assisted by audiovisual media. Secondly, it describes the level of explanatory text writing skills of grade XI students of SMK Negeri 9 Padang after using a problem based learning model assisted by audiovisual media. Third, analyze the influence of the use of problem based learning models assisted by audiovisual media on the ability to wite explanatory text for grade XI students of SMK Negeri 9 Padang. This type of research is quantitative research with experiment methods (quasi experiment). The populasi in this study amounted to 174 students and the sample of this study was class XI PH 1 and 2 totaling 32 students. Based on the results of the study, there are three things below. First, the explanatory text writing skills before using the problem based learning model assisted by audiovisual media are of sufficient qualifications (60,08). Second, the explanatory text writing skills after using the problem based learning model assisted by audiovisua media are in good qualifications (78,08). Third, there is a significant influence in the use of problem based learning model assisted by audiovisual media based on the results of the t-test that the working hypothesis (H1) is accepted at a significant level of 95% and dk=(n-1) because tcount>ttable (4,98>1,70) Kata Kunci: Pengaruh, Model Problem Based Learning Berbantuan Media Audiovisual, Keterampilan Menulis Teks Eksplanasi